Perkembangan Keberagamaan Individu Pada Usia Remaja Dalam Perspektif Psikologi Agama - Arya Pramudita; Chaza Afida Amna; Aruni Qurrota Ayun; Carissa Anya Agfalisha Hananto; Arep Kurniawan; Farida Musyrifah (Elsalima (Salam Institute), 2025)
Psychology of religion is a branch of psychology that studies human behavior in relation to their religious beliefs, as well as how it relates to the stages of age development. One of the important phases in an individual's life span is adolescence. Adolescence is a transitional period, where a person moves from childhood to adulthood. This phase is often considered a gray area, as adolescents are not fully included in either the child or adult category. In this phase, adolescents are still not fully able to manage their physical and psychological functions, so it is often referred to as a transitional period. The purpose of this study is to examine the development of the religious soul during adolescence, also known as the murahiqah period. The method we use in this research is a qualitative approach through library research, focusing on literature materials including books, journals, and articles. This approach aims to draw relevant conclusions from various points of view. In analyzing the data, we used content analysis techniques by collecting various sources. The results show that the religious development of adolescents includes aspects of thought and mental growth, the development of moral and social feelings, as well as attitudes and reading interests possessed by adolescents.